Análise de domínio para avaliação de tesauros: uma experiência com a cadeia produtiva do calçado no Brasil - Lorenzon, Emilena Josimari [UNESP] (2011)
We tried to solve the problem of footwear production chain in Brazil, while specialized fields, it does not have an indexing language to specifically include the organization and representation of your information, showing that the only existing tool for controlled vocabulary in the productive sector, microthesaurus called the Leather and Footwear, produced by the National Service of Industrial Learning - SENAI is not enough to organize now, all the content covered within the area in question. We utilize the theoretical assumptions of John Swales on domain analysis, and discursive communities, applying the following methodology: 1) delineation of the domain (definition of where it begins and ends), using the methodological principles proposed by Tennis (2003) and approaches the 11 Hjørland (2001, 2002) for analysis, limiting it through their areas of modulation and the degree of specialization, 2) identification of users of the terminology, ie the discursive communities that domain, 3) selection a very specific category and two facets to the identification of terms, 4) definition and selection of the corpus for the study, 5) use of a technology for semi-automatic extraction of terms in the corpus, eliminating those that are not specific in the area, with the aid of an industry expert, and finally 6) comparison of some terms, selected by their degree of specificity in the field, with the terms described in microthesaurus analyzed. It was intended to research to verify the possibility of evaluating thesauri from the domain analysis as the prospects of Swales. This chain was chosen because the researcher's professional involvement in the process of organizing their information and knowledge